Pengembangan Bahan Ajar Digital Berbantuan Canva Siswa Kelas IV UPT SDN 064034 Medan - Silvia, Silvia; Muhammad Noer Fadlan (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to develop Canva-assisted digital teaching materials using the Discovery Learning model for Civic Education (PKn) on the topic "Cooperation in My Environment" to improve fourth-grade students’ learning motivation at UPT SDN 064034 Medan. This research applied the Research and Development (R&D) method using the ADDIE model, involving analysis, design, development, implementation, and evaluation. The developed product was validated by experts, yielding very high results: 81.05% (material), 89.52% (teaching material), 100% (module), and 83.52% (teacher), with an overall validity of 88.52%, categorized as “very valid.” The materials were considered practical and effectively implemented during learning. Effectiveness was measured through student responses and learning motivation improvement, both showing highly positive results. Overall, the Canva-assisted digital teaching materials meet the criteria of being valid, practical, and effective, and significantly enhance students’ motivation in Civic Education lessons.